A large-scale RNAi screen identifies functional classes of genes shaping synaptic development and maintenance. - Valakh, V.; Naylor, S.A.; Berns, D.S.; Diantonio, A. (Developmental Biology, 2012)
Neuronal circuit development and function require proper synapse formation and maintenance. Genetic screens are one powerful method to identify the mechanisms shaping synaptic development and stability. However, genes with essential roles in non-neural tissues may be missed in traditional loss-of-function screens. In an effort to circumvent this limitation, we used neuron-specific RNAi knock down in Drosophila and assayed the formation, growth, and maintenance of the neuromuscular junction (NMJ). We examined 1970 Drosophila genes, each of which has a conserved ortholog in mammalian genomes. Knock down of 158 genes in post-mitotic neurons led to abnormalities in the neuromuscular system, including misapposition of active zone components opposite postsynaptic glutamate receptors, synaptic terminal overgrowth and undergrowth, abnormal accumulation of synaptic material within the axon, and retraction of synaptic terminals from their postsynaptic targets. Bioinformatics analysis demonstrates that genes with overlapping annotated function are enriched within the hits for each phenotype, suggesting that the shared biological function is important for that aspect of synaptic development. For example, genes for proteasome subunits and mitotic spindle organizers are enriched among the genes whose knock down leads to defects in synaptic apposition and NMJ stability. Such genes play essential roles in all cells, however the use of tissue- and temporally-restricted RNAi indicates that the proteasome and mitotic spindle organizers participate in discrete aspects of synaptic development. In addition to identifying functional classes of genes shaping synaptic development, this screen also identifies candidate genes whose role at the synapse can be validated by traditional loss-of-function analysis. We present one such example, the dynein-interacting protein NudE, and demonstrate that it is required for proper axonal transport and synaptic maintenance. Thus, this screen has identified both functional classes of genes as well as individual candidate genes that are critical for synaptic development and will be a useful resource for subsequent mechanistic analysis of synapse formation and maintenance.